Between Waves and Chimneys The Transformation of Fishermen Profession to Industry in Gresik Region 1996-2000: Transformasi Profesi Nelayan ke Industri di Wilayah Gresik Tahun 1996-2000 - Devi Muzrotun Naimah; Carolina Santi Muji Utami (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This article analyzes the shift from fishermen to industrial workers in the coastal region of Gresik between 1996 until 2000. Traditionally, Gresik’s coastal communities relied on fisheries due to the region’s significant maritime history. However, the industrial wave in the New Order era, marked by the establishment of large factories like PT Semen Gresik and PT Petrokimia, initiated an economic transformation. Based on interviews from local residents and using archival data, this study focused on the ecological, socioeconomic, and overexploitation factors leading to this shift using a historical framework. This study indicates the availability of industrial jobs led to a greater migratory pull due to increased social security and income stability. Such changes not only transformed the economic landscape of the region but also the social identity by undermining traditions and collectivist frameworks. The study broadens the scope of understanding how the convergence of local conditions and national economic policies brings about significant social change.